(untitled) (Journal of Computational Innovation and Analytics (JCIA), 2024)
Quite recently, marketers have used memes because they entice customers’ attention. It serves as a means to have a dialogue between customers and companies. Some companies would even hire people to browse the internet for relevant memes. The emergence of Generation Z, who are digital natives, has brought significant changes to how businesses interact with their target audience. One potential strategy is to use digital memes as a marketing tool to engage them. The study, using 271 respondents, investigates the use of the aforementioned tool to determine its appropriateness in lead generation based on the Attention, Interest, Desire, Action (AIDA) model. Using the software Analysis of Moment Structures (AMOS), a descriptive exploratory design using Structural Equation Modeling (SEM) was used to investigate the relationship between the different variables in the study. The findings show that attention impacts interest, interest influences desire, and desire significantly affects action at a significance level of p < 0.01. The study revealed that Digital memes are an effective tool that can be utilized to generate leads. Businesses can use digital memes to engage with the Generation Z segment. However, prudence in creating memes must align the message with corporate values and be relevant to the target audience.